Skip to content
Related Articles

Related Articles

Improve Article
Save Article
Like Article

Class 12 RD Sharma Solutions – Chapter 11 Differentiation – Exercise 11.6

  • Last Updated : 11 Feb, 2021

Question 1. If y=\sqrt{x+\sqrt{x+\sqrt{x+....to\ \infin}}}, prove that \frac{dy}{dx}=\frac{1}{2y-1}

Solution:

We have, y=\sqrt{x+\sqrt{x+\sqrt{x+....to\ \infin}}}

Hey! Looking for some great resources suitable for young ones? You've come to the right place. Check out our self-paced courses designed for students of grades I-XII

Start with topics like Python, HTML, ML, and learn to make some games and apps all with the help of our expertly designed content! So students worry no more, because GeeksforGeeks School is now here!

 



⇒ y=\sqrt{x+y}

Squaring both sides, we get,

y2 = x + y

⇒2y\frac{dy}{dx}=1+\frac{dy}{dx}\\ ⇒\frac{dy}{dx}(2y-1)=1\\ ⇒\frac{dy}{dx}=\frac{1}{2y-1}

Question 2. If y=\sqrt{cosx+\sqrt{cosx+\sqrt{cosx+ ....\ to\ \infin}}}, prove that \frac{dy}{dx}=\frac{sinx}{1-2y}

Solution:

We have, y=\sqrt{cosx+\sqrt{cosx+\sqrt{cosx+ ....\ to\ \infin}}}

⇒ y = \sqrt{cosx+y}

Squaring both sides, we get,



y2 = cos x + y

⇒ 2y\frac{dy}{dx}=-sinx+\frac{dy}{dx}\\ ⇒ \frac{dy}{dx}(2y-1)=-sinx\\ ⇒ \frac{dy}{dx}=\frac{-sinx}{1-2y}\\ ⇒ \frac{dy}{dx}=\frac{sinx}{1-2y}

Question 3. If y=\sqrt{logx+\sqrt{logx+\sqrt{logx+ ....\ to\ \infin}}}, prove that (2y-1)\frac{dy}{dx}=\frac{1}{x}

Solution:

We have, y=\sqrt{logx+\sqrt{logx+\sqrt{logx+ ....\ to\ \infin}}}

⇒ y=\sqrt{logx+y}

Squaring both sides, we get,

y2 = log x + y

⇒ 2y\frac{dy}{dx}=\frac{1}{x}+\frac{dy}{dx}\\ ⇒ \frac{dy}{dx}(2y-1)=\frac{1}{x}

Question 4. If y=\sqrt{tanx+\sqrt{tanx+\sqrt{tanx+ ....\ to\ \infin}}} , prove that \frac{dy}{dx}=\frac{sec^2x}{2y-1}

Solution:

We have, y=\sqrt{tanx+\sqrt{tanx+\sqrt{tanx+ ....\ to\ \infin}}}



⇒ y =\sqrt{tanx+y}

Squaring both sides, we get,

y2 = tan x + y

⇒2y\frac{dy}{dx}=sec^2x+\frac{dy}{dx}\\ ⇒\frac{dy}{dx}(2y-1)=sec^2x\\ ⇒\frac{dy}{dx}=\frac{sec^2x}{2y-1}

Question 5. If y=(sinx)^{(sinx)^{(sinx)^{...\infin}}} , prove that \frac{dy}{dx}=\frac{y^2cotx}{(1-y\ logsinx)}

Solution:

We have, y=(sinx)^{(sinx)^{(sinx)^{...\infin}}}

⇒ y = (sin x)y

Taking log on both sides,

log y = log(sin x)y

⇒ log y = y log(sin x)



⇒\frac{1}{y}\frac{dy}{dx}=y\frac{d}{dx}\{log(sinx)\}+log\ sinx\frac{dy}{dx}\\ ⇒\frac{1}{y}\frac{dy}{dx}=y\left(\frac{1}{sinx}\right)\frac{d}{dx}(sinx)+log\ sinx\frac{dy}{dx}\\ ⇒\frac{dy}{dx}\left(\frac{1}{y}-log\ sinx\right)=\frac{y}{sinx}(cosx)\\ ⇒\frac{dy}{dx}\left(\frac{1-y\ log\ sinx}{y}\right)=y\ cotx\\ ⇒\frac{dy}{dx}=\frac{y^2cotx}{1-y\ log\ sinx}

Question 6. If y=(tanx)^{(tanx)^{(tanx)^{...\infin}}} , prove that \frac{dy}{dx}=2\ at\ x=\frac{\pi}{4}

Solution:

We have, y=(tanx)^{(tanx)^{(tanx)^{...\infin}}}

⇒ y = (tan x)y

Taking log on both sides,

log y = log(tan x)y

⇒ log y = y log tan x

Differentiating with respect to x using chain rule,

⇒ \frac{1}{y}\frac{dy}{dx}=y\frac{d}{dx}\{\log\ tanx\}+\log\ tan\frac{dy}{dx}\\ ⇒ \frac{1}{y}\frac{dy}{dx}=\frac{y}{tanx}\frac{d}{dx}\{tanx\}+\log\ tan\frac{dy}{dx}\\ ⇒\frac{dy}{dx}\left(\frac{1}{y}-\log tanx\right)=\frac{y}{tanx}sec^2x\\ ⇒\frac{dy}{dx}=\frac{y}{tanx}sec^2x\times\left(\frac{y}{1-y\log tanx}\right)\\

Now,



\left(\frac{dy}{dx}\right)_{x=\frac{\pi}{4}}=\frac{y\ sec^2\left(\frac{\pi}{4}\right)}{tan\left(\frac{\pi}{4}\right)}\times\frac{y}{1-y\ \log tan\left(\frac{\pi}{4}\right)}\\ ⇒\left(\frac{dy}{dx}\right)_{x=\frac{\pi}{4}}=\frac{y^2(\sqrt{2})^2}{1(1-y\log\ tan1)}\\ ⇒\left(\frac{dy}{dx}\right)_{x=\frac{\pi}{4}}=\frac{2(1)^2}{(1-0)}\ \ \ \ \ \left[\because\ (y)_{\frac{\pi}{4}}=\left(tan\frac{\pi}{4}\right)^{\left(tan\frac{\pi}{4}\right)^{\left(tan\frac{\pi}{4}\right)^{...\infin}}}=1\right]\\ ⇒\left(\frac{dy}{dx}\right)_{x=\frac{\pi}{4}}=2

Question 7. If y=e^{x^{e^x}}+x^{e^{x^e}}+e^{x^{x^e}} , prove that e^{x^{e^x}}\times x^{e^{x}}\left\{\frac{e^x}{x}+e^x\times \log x\right\}+e^{e^{e^x}}\times e^{e^{^x}}\left\{\frac{1}{x}+e^x\times \log x\right\}+e^{x^{x^e}}x^{x^{e}}\times x^{e-1}\{1+e\log x\}

Solution:

We have, y=e^{x^{e^x}}+x^{e^{x^e}}+e^{x^{x^e}}

⇒ y = u + v + w

\frac{dy}{dx}=\frac{du}{dx}+\frac{dv}{dx}+\frac{dw}{dx}\ \ ...(i)

where u=e^{x^{e^x}},\ v=x^{e^{x^e}}\ and\ w=e^{x^{x^e}}

Now, u=e^{x^{e^x}}\ \ \ \ \ ....(ii)

Taking log on both sides,

\log u=\log e^{x^{e^x}}\\ \Rightarrow\log u=x^{e^{x}}\log e\\ \Rightarrow\log u=x^{e^{x}}\ \ \ ...(iii)\\ \log \log u=\log x^{e^{x}}\\ \Rightarrow\log \log u = e^x\log x

Differentiating with respect to x,



\Rightarrow\frac{1}{\log u}\frac{d}{dx}(\log u)=e^x\frac{d}{dx}(\log x)+\log x\frac{d}{dx}(e^x)\\ \Rightarrow\frac{1}{\log u}\frac{1}{u}\frac{du}{dx}=\frac{e^x}{x}+e^x\log x\\ \Rightarrow\frac{du}{dx}=u\log u\left[\frac{e^x}{x}+e^x\log x\right]\\ \Rightarrow\frac{du}{dx}=e^{x^{e^x}}\times x^{e^{x}}\left[\frac{e^x}{x}+e^x\log x\right]\\ Now,\ v=x^{e^{x^e}}\ \ \ \ \ ...(iv)

Taking log on both sides,

\log v=\log x^{e^{e^x}}\\ \Rightarrow\log v = e^{e^{x}}\log x

Taking log on both sides

\Rightarrow\frac{1}{\log w}\frac{d}{dx}(\log w)=x^e\frac{d}{dx}(\log x)+\log x\frac{d}{dx}(x^e)\\ \Rightarrow\frac{1}{\log w}\left(\frac{1}{w}\right)\frac{dw}{dx}=x^e\left(\frac{1}{x}\right)+\log xex^{e-1}\\ \Rightarrow\frac{dw}{dx}=w\log w[x^{e-1}+e\log xx^{e-1}]\\ \Rightarrow\frac{dw}{dx}=e^{x^{x^e}}x^{x^{e}}x^{e-1}(1+e\log x)\\

Using equation in equation (i), we get

\frac{dy}{dx}=e^{x^{e^x}}{x^{e^x}}\left[\frac{e^x}{x}+e^x\log x\right]+x^{e^{e^x}}\times e^{e^x}\left[\frac{1}{x}+e^x\log x\right]+e^{x^{x^e}}{x^{x^e}}x^{e-1}(1+e\log x)

Question 8. If y=(cosx)^{(cosx)^{(cosx)^\ ...\infin}}, Prove that \frac{dy}{dx}=\frac{y^2tanx}{(1-y\log cosx)}

Solution:

We have, y=(cosx)^{(cosx)^{(cosx)^\ ...\infin}}

⇒ y = (cos x)y

Taking log on both sides,

log y = log(cos x)y

⇒ log y = y log (cos x)

Differentiating with respect to x using chain rule,

\frac{1}{y}\frac{dy}{dx}=y\frac{d}{dx}\{\log cosx\}+\log cos x\frac{dy}{dx}\\ \Rightarrow\frac{1}{y}\frac{dy}{dx}=y\left(\frac{1}{cosx}\right)\frac{d}{dx}(cosx)+\log cosx\frac{dy}{dx}\\ \Rightarrow\frac{dy}{dx}\left(\frac{1}{y}-\log cosx\right)=\frac{y}{cosx}(-sinx)\\ \Rightarrow\frac{dy}{dx}\left(\frac{1-y\log cosx}{y}\right)=-y\ tanx\\ \Rightarrow\frac{dy}{dx}=-\frac{y^2tanx}{(1-y\log cosx)}




My Personal Notes arrow_drop_up
Recommended Articles
Page :

Start Your Coding Journey Now!